Voprosy taktiki v strelkovych vidach sporta - Tarasova, L. V. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The tactics of competitive activity in shooting kinds of sports differs by it's individuality. A shooter does not need to consider the technical-tactical characteristics of the contender. The tactics is determined as the ability of a shooter to organize the behavior and the actions under varied conditions of an environment and changeability of psychophysical conditions of an organism for the realizations of the most effective program of each shot and exercise as the whole.